Prevalence of linguatulosis in cattle (Bos taurus) in a slaughtering house of Chile - Ramos G., Juan José (2019)
The objective of the present study was to determine the prevalence of linguatulosis in bovine viscera in a slaughter house in Curicó, VII Region, Chile. The macroscopic examination of the liver, lungs, heart and the mediastinal, mesenteric and hepatic lymph nodes of 269 cattle was performed. In cases of lesions compatible with linguatulosis, the viscera were considered positive and these were observed under a stereoscope to reach the etiological diagnosis, considering as positive the lesions that presented one or more nymphs. The results showed that 11.89% of the cattle presented lesions compatible with linguatulosis in the viscera analysed and only one (0.37%) presented the positive etiological diagnosis of Linguatula serrata nymphs. The largest number of compatible lesions was found in the liver (81.8%), followed by mesenteric lymph nodes (9.1%), hepatic lymph nodes (6.1%) and lungs (3.0%). No lesions were detected in the heart and mediastinal lymph nodes. There is no validated method to identify macroscopic lesions caused by linguatulosis, so the finding of compatible lesions can be biased since these could be caused by other agents. Linguatulosis is non-notifiable disease in Chile, despite being considered as a zoonotic disease and having importance in public health.